THE EFFECT OF THE UTILIZATION OF INFORMATION TECHNOLOGY AND ORGANIZATIONAL CULTURE ON EMPLOYEE MOTIVATION AND PERFORMANCE - Ni Komang Prasiani; Anik Yuesti; Nengah Sudja (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
The purpose of this study is to determine the relationship between organizational culture variables, information technology, and employee performance, whether or not technology plays a role in improving employee performance. The population in this study is the Information System Users (SINERGY) in the Bali Design and Business Institute, consisting of 81 lecturers and employees. Data relating to research variables were collected using questionnaires that were distributed to all respondents and filled in by the respondents themselves based on the respondents' perceptions. Based on the instrument test performed, it was proven that all statement items in the questionnaire are valid and reliable. This study uses Structural Equation Modeling (SEM) analysis. The results indicate that: the use of information technology has a positive and significant effect on motivation. Organizational culture has a positive effect on motivation. The use of information technology has a positive on employee performance. Organizational culture has a positive effect on employee performance. Motivation has a positive and significant effect on employee performance. Keywords: Information Technology, Organizational Culture, Motivation and Employee Performance.